Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences; Vol 11 No 2 (2025): NIU Journal of Social Sciences, Vol. 11 No. 2, June 2025, 2025)
This edition of NIU Journal of Social Sciences focuses on Development Administration, Educational Psychology as well as Social Philosophy. The first part of the Journal addresses issues in Development Administration such as Global Peace, Waste Management Practices, Tourism, Intelectual Property Protection Rights, Petroleum Product Distribution and Logistics as well as Cashless Policy and the Financial Performance of Deposit Money Banks. It is established in one of the papers that many Nigerian tourist centres underutilise the digital marketing opportunities embedded in the social media sphere. It suggests therefore that social media utilisation can accelerate tourism promotion and development in Nigeria as long as tourist centres in the country pay attention to creating share-worthy experiences and cultivating vibrant engagements with tourists. Papers in the second part are on Educational Psychology. It is revealed in one of the papers in this section that peer collaboration, teacher feedback, and Science, Technology, Engineering and Mathematics (STEM) career exposure play pivotal roles in shaping girls’ attitudes towards STEM subjects. Hence, the study recommends that schools should provide regular teacher training programs to improve the effectiveness of feedback strategies and implement structured feedback mechanisms to provide timely and constructive support to foster girls’ interest in STEM. In the last section on Organizational Behaviour, one of the papers reveals that beliefs and attitudes were not statistically significant in shaping consumer buying decisions in either outlet type. Furthermore, psychological factors play a vital role in influencing consumer purchasing decisions in both retail formats. The paper therefore recommends that retailers develop a marketing tactics effective and suitable to motivate at the same time influence consumers’ buying behavior, targeting the factors that determines their purchase decisions to include past experience, product awareness, social status, personal values, and emotional responses. Readers are advised to make proper use of the ideas presented by the various authors in this issue of NIU Journal of Social Sciences . Some of these papers are empirical in nature while others have theoretical base. Each of them focuses on one specific social and management problem or the other; trying to proffer solutions to them.